2006
DOI: 10.1080/00365520510024278
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in cirrhotic patients with and without ascites

Abstract: Malnutrition is a common finding in patients with liver cirrhosis. Malnutrition has been shown to be associated with increased morbidity and mortality. Its pathogenesis remains unclear but both poor dietary intake and increased energy expenditure have been reported.Spontaneous bacterial peritonitis is an important clinical problem in cirrhotics. It may occur as a consequence of repeated access of bacteria from the intestinal lumen (translocation) to the mesenteric lymph nodes. One of the mechanisms proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 162 publications
(386 reference statements)
0
56
2
1
Order By: Relevance
“…Some authors have shown an association between increased intestinal permeability and severity of liver cirrhosis as assessed by the Child-Pugh classification [68,69,70], but others have failed to reproduce these results [71,72,73]. Increased permeability on hospital admission has also been related to some complications of liver cirrhosis [67], although the published studies are not always unanimous [74].…”
Section: Intestinal Hyperpermeabilitymentioning
confidence: 96%
“…Some authors have shown an association between increased intestinal permeability and severity of liver cirrhosis as assessed by the Child-Pugh classification [68,69,70], but others have failed to reproduce these results [71,72,73]. Increased permeability on hospital admission has also been related to some complications of liver cirrhosis [67], although the published studies are not always unanimous [74].…”
Section: Intestinal Hyperpermeabilitymentioning
confidence: 96%
“…The concept of altered intestinal per meability is important and has been implicated in a number of pathological situations, including celiac disease associated with antigen permeability, allergic intestinal diseases such as digestive hypersensitivity, inflammatory diseases such as Crohn's disease, ulcerative colitis, acute pancreatitis, alcoholic liver disease and LC associated with substance permeability during inflammation [5,21,22] . The pathogenic mechanisms implicated in the failure of intestinal barrier in cirrhosis have not been fully elucidated as yet and remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of PEG in ascites might have caused a lower urinary excretion rate and thus underestimated possible permeability changes in patients with ascites. However, Kalaitzakis et al assessing intestinal permeability with 51Cr-EDTA concluded that a loss of 51Cr-EDTA into the ascitic compartment was unlikely and paracentesis had no significant effect on the urinary 51Cr-EDTA excretion, which suggests that ascites in itself does not unduly affect the test results [5] . In the present study, ascitic fluid from three cirrhotic patients was tested for PEG and it was not detected; therefore, the possibility of lower urinary excretion rates due to distribution of PEG in ascites can be ruled out.…”
Section: Cirrhotics Without Ascites (N = 27)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors that lead to loss of the intestinal barrier function is the structural damage of the intestinal wall with increasing permeability of bacteria into systemic circulation, especially in advanced stages of liver disease that is already associated with altered bacterial flora [35,36] . Portal hypertension induces enteropathy with intestinal wall thickening, capillary dilatation, edema of the lamina propria and reduction of villus/crypt ratio that can influence bacterial translocation [37] .…”
Section: Pathophysiologymentioning
confidence: 99%